2021
DOI: 10.1155/2021/8885093
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Induces Apoptosis and Inhibits Proliferation, Invasion, and Migration of Human Cervical Carcinoma HeLa Cells

Abstract: Purpose. To study the effect of osthole extract on proliferation, migration, invasion, and apoptosis of human cervical carcinoma HeLa cells and investigate its underlying mechanism. Methods. HeLa cells were exposed to osthole at various concentrations. Cell viability, migration, and invasion were detected by MTT assay, scratch wound-healing assay, and invasion assay, respectively. The proportion of cells undergoing apoptosis was analyzed by flow cytometry. Western blot and RT-qPCR were performed to determine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Xu et al revealed that osthole suppresses gastric cancer cell proliferation [ 36 ]. Yin et al demonstrated that osthole could inhibit proliferation, invasion, and migration of human cervical cancer [ 37 ]. Sun et al revealed that osthole induces apoptosis in human tongue cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al revealed that osthole suppresses gastric cancer cell proliferation [ 36 ]. Yin et al demonstrated that osthole could inhibit proliferation, invasion, and migration of human cervical cancer [ 37 ]. Sun et al revealed that osthole induces apoptosis in human tongue cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al determined that osthole was able suppress the proliferation of endometrial cancer cells by inhibiting the PI3K-AKT pathway [ 11 ]. Yin et al discovered that osthole could block the Wnt/β-catenin pathway, influencing the proliferation and invasion of human cervical carcinoma [ 37 ]. Dai et al concluded that osthole could inhibit triple-negative breast cancer by suppressing Stat3 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al revealed that osthole suppresses gastric cancer cell proliferation [26]. Yin et al demonstrated that osthole could inhibit proliferation, invasion, and migration of human cervical cancer [27]. Sun et al revealed that osthole induces apoptosis in human tongue cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al determined that osthole was able suppress the proliferation of endometrial cancer cells by inhibiting the PI3K-AKT pathway [9]. Yin et al discovered that osthole could block the Wnt/β-catenin pathway, in uencing the proliferation and invasion of human cervical carcinoma [27]. Dai et al concluded that osthole could inhibit triple-negative breast cancer by suppressing Stat3 [37].…”
Section: Discussionmentioning
confidence: 99%
“…IC 50 values of Osthole on HeLa and Me-180 were 45.01 ± 3.91 μM and 88.95 ± 0.13 μM, respectively, while values were 8.35 ± 1.62 μM and 10.29 ± 0.18 μM for LRRK, respectively ( Pan et al, 2021 ). Osthole (50, 100, 200 μg/ml) extract also effectively promoted apoptosis and inhibited cellular proliferation, migration, and invasion potential in a cervical cancer cell line (HeLa) in a dose-dependent manner through inactivation of the Wnt/ β -catenin pathway ( Yin et al, 2021 ).…”
Section: Anticancer Mechanism Of Osthole In Various Organ Systemsmentioning
confidence: 99%